Women in Mexican diplomacy: history and political, social, economic and cultural barriers - Sepúlveda Chapa, Patricia Rebeca (2025)
Since the last few decades, feminism has been incorporated into the discipline of International Relations (IR), which has represented an important theoretical and practical advance in international dynamics with a gender perspective. Based on the notion that disparities between women and men have an impact on power structures, the question of including women’s experiences and voices in the analysis of international politics has increased. The purpose of this article is to answer the following questions: where are the women in Mexican diplomacy? Which are the most important barriers or obstacles that Mexican women have faced to be part of the Mexican Foreign Service? Considering that, although Mexico adopted a feminist foreign policy, women do not occupy the highest hierarchical positions in the public sector. To further advance the study and its application in diplomatic practice, key contributions made by eminent feminist scholars such as J. Ann Tickner and Cynthia Enloe are also examined. This article presents a literature review as a methodological approach on the influence of Feminism in the discipline and on the participation of Mexican women in the country’s public diplomacy.